DINAMIKA PEMIKIRAN ISLAM DI INDONESIA - Mahfud Mahfud (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
This article attempts to explain Indonesian Islamic thought. Islam, which is areligion where all of its values come from God's revelations, must ultimatelyintersect with human culture. Ratioanalism which relies on the use of reason as atool to comprehend religious law comprehensively. Ratioanlis, progressive Islam isan inseparable part of the history of diversity in Indonesia. Islamic thought inIndonesia was started in the 1970s by Nurcholish Madjid. Another thinker whobecame a pioneer from the birth of Indonesian Islamic thought was AbdurrahmanWahid in the 1980s. Harun Nasutian, Moeslim Abdurrahman are figures who havehad an influence on Islamic thought in Indonesia. The ideas of Islamic thoughtinitiated by some of these figures later became the beginning of the birth of liberalIslam which was a form of thought that was quite controversial among Muslims, butthis understanding later became part of the dynamics of Indonesian Islamic thoughtas a new form and a new offer in the Islamic world, especially an offer to look atIslam more rationally. The use of reason in this understanding is characteristic, butthe use of reason here is intended to bring Islam from stagnation of thought